Hernia and Cancer: The Points Where the Roads Intersect - Kulacoglu, Hakan; Köckerling, Ferdinand (Frontiers in Surgery, 2019)
Introduction: This review aimed to present common points, intersections and potential interactions or mutual effects for hernia and cancer. Besides direct relationships, indirect connections and possible involvements were searched. Materials and Methods: A systematic search of PubMed database was performed in July 2018 as well as a search of relevant journals and reference lists. The total number of screened articles was 1422. Some articles were found in multiple different searches. A last PubMed search was performed during manuscript writing in December 2018 to update the knowledge. Eventually 427 articles with full text were evaluated, and 264 included, in this review. Results: There is no real evidence for a possible common etiology for abdominal wall hernias and any cancer type. The two different diseases had been found to have some common points in the studies on genes, integrins, and biomarkers, however, to date no meaningful relationship has been identified between these points. There is also some, albeit rather conflicting, evidence for inguinal hernia being a possible risk factor for testicular cancer. Neoadjuvant or adjuvant therapeutic modalities like chemotherapy and radiotherapy may cause postoperative herniation with their adverse effects on tissue repair. Certain specific substances like bevacizumab may cause more serious complications and interfere with hernia repair. There are only two articles in PubMed directly related to the topic of “hernia and cancer”. In one of these the authors claimed that there was no association between cancer development and hernia repair with mesh. The other article reported two cases of squamous-cell carcinoma developed secondary to longstanding mesh infections. Conclusion: As expected, the relationship between abdominal wall hernias and cancer is weak. Hernia repair with mesh does not cause cancer, except for longstanding prosthetic material infections. However, there are some intersection points between these two disease groups which are worthy of research in the future.